Pengaruh Pemberian Teh Chamomile Terhadap Kualitas Tidur Pada Ibu Postpartum Blues Di Klinik Pratama Sehati Husada Kecamatan Biru-Biru Kabupaten Deli Serdang Tahun 2024 - Hayati, Erlina .; Sari, Husna; Oktapiani, Anggun Tri (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Sleep disorders are a condition that can cause problems with a person's sleep patterns. Like waking up every night, and having trouble sleeping. So, researchers are looking for an alternative solution for mothers who experience this by giving herbal drinks such as chamomile tea. Chamomile tea contains flavonoid compounds, namely apigenin, which binds to benzodiazepine receptors in the brain, providing a calming feeling. The type used in this research is quantitative research with a quasi-experimental design to determine the pretest posttest scores. For sampling, the Pittsburgh Sleep Quality (PSQI) questionnaire was used to determine the sleep quality score of respondents. Based on the results of research conducted by researchers on 20 respondents, before being given chamomile tea, 14 people were in the moderate category, 6 people were in the bad category, and after being given chamomile tea there were 14 people in the good category, and 6 people were in the moderate category. Researchers can conclude that there was an improvement after it was given. The results of the normality test that the researcher carried out obtained a p value of 0.00 (<0.05). Where the data was not normally distributed, therefore the researcher switched to the Wilcoxon Test. It can be interpreted that in this study if the p value is 0.00 then Ha is accepted while H0 is rejected or there is an influence of giving chamomile tea.